Cablegate and the continuing US penetration in Brazil - Zirker, Daniel (Tensões Mundiais, 2018)
Jan Black outlined the US penetration of Brazilian politics in the 1960s and 1970s, including the linkages with military and business elites, revealing their compromise on national sovereignty. Based on cables released by WikiLeaks, this study shows a renewed emphasis by the US government to manipulate Brazilian domestic and foreign policies in the late 1990s and 2000s.